2015
DOI: 10.1111/cmi.12491
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cell surface transport and lipid raft localization by the cytoplasmic tail of the influenza virus hemagglutinin

Abstract: Viral glycoproteins are highly variable in their primary structure, but on the other hand feature a high functional conservation to fulfil their versatile tasks during the pathogenic life cycle. Typically, all protein domains are optimized in that indispensable functions can be assigned to small conserved motifs or even individual amino acids. The cytoplasmic tail of many viral spike proteins, although of particular relevance for the virus biology, is often only insufficiently characterized. Hemagglutinin (HA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…For enveloped viruses, both cytoplasmic and transmembrane structural proteins use palmitoylation as a mechanism to achieve or enhance membrane association during budding. Palmitoylation of influenza virus hemagglutinin, a transmembrane protein, increases its association with membrane microdomains, where it interacts with the M2 protein during budding (50)(51)(52). In herpes simplex virus, the tegument protein UL51 relies on palmitoylation for association with the Golgi membrane, where secondary envelopment occurs (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…For enveloped viruses, both cytoplasmic and transmembrane structural proteins use palmitoylation as a mechanism to achieve or enhance membrane association during budding. Palmitoylation of influenza virus hemagglutinin, a transmembrane protein, increases its association with membrane microdomains, where it interacts with the M2 protein during budding (50)(51)(52). In herpes simplex virus, the tegument protein UL51 relies on palmitoylation for association with the Golgi membrane, where secondary envelopment occurs (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that influenza A virus HA and NA are associated with lipid raft microdomains (Barman and Nayak, 2000; Zhang et al, 2000; Scolari et al, 2016), which play pivotal roles in apical PM trafficking in polarized cells (Simons and Ikonen, 1997; Rodriguez-Boulan et al, 2005; Rog and Vattulainen, 2014). Previous studies on HA have shown that the disruption of HA association with lipid rafts by the use of non-raft mutants and treatment of cholesterol-lowering drugs cause a delay or block in TGN-to-apical PM trafficking of HA (Keller and Simons, 1998; Ohkura et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…HA-CT (Siche et al 2015) plays an important role in virus replication (Imai et al 2012), viral infectivity (Siche et al 2015), and virus entry into host cells (Scolari et al 2016). Although its functions have been well studied, little is known about the immunogenicity and sub-localization of HA-CT.…”
mentioning
confidence: 99%